1989
DOI: 10.1111/j.1095-8649.1989.tb02964.x
|View full text |Cite
|
Sign up to set email alerts
|

The palatability of amino acids and related compounds to rainbow trout, Salmo gairdneri Richardson

Abstract: Using a behavioural assay, the palatability of urea, taurine, betaine and the 20 common amino acids (L-isomers) to rainbow trout was determined. The trout responded positively only to aqueous solutions of leucine, isoleucine, proline, phenylalanine, tryptophan, methionine, glutamate, arginine, taurine and urea. Proline, the most effective compound, was active at M but not 1 0 -5~. Palatibility was not directly related to test solution pH; concentration and molecular structure apparently played a greater role. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 38 publications
7
58
0
Order By: Relevance
“…This finding is in agreement with earlier findings in which individual variabilities in taste preferences within the same species have been found in 1 out of 25 rainbow trout (Jones, 1989) and in 3 of 11 individuals of the same species (Mearns et al, 1987). Additionally, common carp (Cyprinus carpio) exhibit individual differences in their acceptance of the single amino acids l-cysteine (97.3%) and l-glutamic acid (41.8%) (Kasumyan, 2000).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in agreement with earlier findings in which individual variabilities in taste preferences within the same species have been found in 1 out of 25 rainbow trout (Jones, 1989) and in 3 of 11 individuals of the same species (Mearns et al, 1987). Additionally, common carp (Cyprinus carpio) exhibit individual differences in their acceptance of the single amino acids l-cysteine (97.3%) and l-glutamic acid (41.8%) (Kasumyan, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…The test feed contained four times more betaine than the control feed, and betaine is a known attractant for several fish species (Kasumyan and Doving, 2003;Yamashita et al, 2006) that is typically found in marine invertebrates such as mussels (Meyers, 1987). Although betaine was not found to be a stimulant for rainbow trout (Jones, 1989) or Chinook salmon (Hughes, 1993), the highly species-specific taste preferences of fish (Kasumyan and Doving, 2003) indicate that betaine cannot be excluded as an attractive substance for Arctic charr. Additionally, due to manufacturing difficulties, the Baltic Sea test feed had slightly more fat on the surface that was not completely absorbed by the pellet.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Lyophilised shrimp extract has been used in ®sh behavioural experiments to evoke or enhance feeding activity. 33 It is important to remark that the lower substitution levels supported better growth rates in tilapia in comparison with the higher levels (Fig 3). These results are in accord with Espe et al, 29 who reported a similar effect for low inclusion levels (15%) using ®sh silage in Atlantic salmon diets.…”
Section: Discussionmentioning
confidence: 99%
“…There is a fair amount of free amino acids produced in the hydrolysis process of fish silage, and these may have acted as attractants (Jones 1989;Berge and Storebakken 1996). Chou and Shiau (1996) determined the optimal dietary lipid level for maximal growth of O. niloticus × O. aureus as 12% and minimal requirement as 5%.…”
Section: Downloaded By [New York University] At 16:45 13 June 2015mentioning
confidence: 99%